A scraper's life history: Morpho-techno-functional and use-wear analysis of Quina and demi-Quina scrapers from Qesem Cave, Israel. (4th April 2016) - Lemorini, Cristina; Bourguignon, Laurence; Zupancich, Andrea; Gopher, Avi; Barkai, Ran
Abstract: A sample of Quina and demi-Quina scrapers from the Yabrudian levels at Qesem Cave has been studied through an integrated approach, combining techno-morpho-functional and use-wear analyses. The potential of this approach is shown using the data obtained and discussed in this paper. Quina and demi-Quina scrapers at Qesem Cave were shaped from blanks originating in different production sequences and were most probably imported to the site as ready-made blanks or as shaped scrapers. In some cases, scrapers and blanks for shaping scrapers were collected from the outside of the cave as is indicated by the patina affecting their surfaces, which was subsequently retouched. At the site, Quina and demi-Quina scrapers were used and re-used (multiple uses on the same edge) and evidence of a long cycle of re-sharpening was recorded as well. The activities carried out with these tools were varied, mostly oriented towards cutting and scraping (both animal materials and plants). Nevertheless, use-wear analysis underlined some distinction between Quina and demi-Quina scrapers: the Quina seem more suitable for working hard and medium-hard materials and the demi-Quina for working softer materials, especially through cutting activities. The different edge morphologies obtained by Quina and demi-Quina retouch are well suited for such functions.